Estimating the contribution of different sources to the burden of human campylobacteriosis and salmonellosis : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Mullner, Petra (Massey University, 2009)
This thesis is concerned with the molecular epidemiology of Campylobacter jejuni and Salmonella in New Zealand and the development of source attribution tools for these pathogens. Although campylobacteriosis is the leading enteric zoonosis worldwide, the pathogen's complex epidemiology and di culties with existing typing schemes, have posed challenges for the control of this disease. The rst study of this thesis gives an overview of existing approaches to microbial risk assessment and source attribution, with particular respect to campylobacteriosis, and describes their advantages and shortcomings. Further, the chapter discusses phenoand genotyping techniques for Campylobacter spp. and the value of including microbial typing data in risk assessments. In the second study, data from a sentinel surveillance site in the Manawatu region was used to investigate the molecular epidemiology of human campylobacteriosis cases. This analysis revealed the presence of a dominant C. jejuni clone, namely sequence type (ST) 474, which accounted for 30.7 % of human cases in the study and identi ed risk factors for infection with ruminant and poultry associated STs. The third study investigated the link between C. jejuni in human cases and samples taken from poultry. By applying epidemiological and population genetic techniques this part of the thesis provided further evidence that poultry is a major contributor to human infection. In the fourth study an existing Bayesian source attribution model was modi ed and consecutively applied to New Zealand's major foodborne zoonoses: campylobacteriosis and salmonellosis. The majority (80 %) of human campylobacteriosis cases attributable to C. jejuni were estimated to have been acquired from poultry sources, whereas wildlife source were estimated to contribute only a minor proportion of cases. In the fth study the Salmonella dataset was descriptively analysed and a large proportion of human cases was found to be caused by `exotic' Salmonella types. In the nal study of this thesis four di erent genetic and epidemiological source attribution methodologies were applied to the same dataset in a comparative modelling framework. iv The studies in this thesis show that epidemiological studies combined with molecular tools and modeling can provide valuable risk-based tools to inform the surveillance and control of zoonotic pathogens. Methods from these studies may be readily applied to the control of other (food borne) zoonoses and provide new opportunities for epidemiological investigations and source attribution modelling of major pathogens.
Keywords: Campylobacter jejuni; Salmonella; Molecular epidemiology; Human campylobaceriosis; Human salmonellosis; New Zealand; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300500 Veterinary Medicine::300503 Epidemiology